Donor/Acceptor Dihydroindeno[1, 2‐a]fluorene and Dihydroindeno[2, 1‐b]fluorene: Towards New Families of Organic Semiconductors. Issue 26 (26th May 2015) - Romain, Maxime; Tondelier, Denis; Geffroy, Bernard; Jeannin, Olivier; Jacques, Emmanuel; Rault‐Berthelot, Joëlle; Poriel, Cyril
Abstract New families of donor/acceptor semiconductors based on dihydroindeno[1, 2‐a]fluorene and dihydroindeno[2, 1‐b]fluorene are reported. Due to the spiro bridges, this new generation of dihydroindenofluorenes allows a spatial separation of HOMO and LUMO, which retains the high ET value of the dihydroindenofluorene backbone and excellent physical properties. This control of the electronic and physical properties has allowed a second generation of dihydroindeno[1, 2‐a]fluorene to be obtained with strongly enhanced performance in green and sky‐blue phosphorescent organic light‐emitting diodes (PhOLEDs) relative to the first generation of materials. To date, this is the highest performance ever reported for a blue PhOLED by using a dihydroindenofluorene derivative. Through this structure–property relationship study, a remarkable difference of performance between syn and anti isomers has also been highlighted. This surprising behaviour has been attributed to the different symmetry of the two molecules, and highlights the importance of the geometry profiles in the design of host materials for PhOLEDs.